Elementary Teacher Education Students’ Short Story Writing Skills through Creative Writing Learning for Short Movie Making - Fauzi, Muhammad Rizal; Pratama, D. Fadly (Mimbar Sekolah Dasar, 2021)
Short story writing skill (short stories) for elementary teacher education students at Cimahi City campus is one of the productive language skills that are said to be still very difficult, considering the skill to write requires multi skills  that involve cognitive skills, cognitive meta, experience, imagination, and the preparation of words and sentences accordingly. Hence, this digital era should be able to make students skilled in utilizing digital devices and products as a medium that helps facilitating them in honing their short story writing skills, one of which is through digital products in the form of short movies. The purpose of this research is to know and elaborate the elementary teacher education students’ skills to write short stories of through short movie making activities in creative writing. This study employs descriptive qualitative through triangulation of data obtained from observations, tests, questionnaires, and documentation. The results showed the students’ skills to write short stories through short movie making activities, it was obtained based on the indicators of short story writing that had been achieved, namely: the suitability of story content, story development creativity, presentation of the plot, characters, point of view, diction, plot, and writing spelling.